Parental kynurenine 3-monooxygenase genotype in mice directs sex-specific behavioral outcomes in offspring - Snezana Milosavljevic; Maria V. Piroli; Emma J. Sandago; Gerardo G. Piroli; Holland H. Smith; Sarah Beggiato; Norma Frizzell; Ana Pocivavsek (Biology of Sex Differences)
Abstract Background Disruptions in brain development can impact behavioral traits and increase the risk of neurodevelopmental conditions such as autism spectrum disorder, attention-deficit/hyperactivity disorder (ADHD), schizophrenia, and bipolar disorder, often in sex-specific ways. Dysregulation of the kynurenine pathway (KP) of tryptophan metabolism has been implicated in cognitive and neurodevelopmental disorders. Increased brain kynurenic acid (KYNA), a neuroactive metabolite implicated in cognition and sleep homeostasis, and variations in the Kmo gene, which encodes kynurenine 3-monooxygenase (KMO), have been identified in these patients. We hypothesize that parental Kmo genetics influence KP biochemistry, sleep behavior and brain energy demands, contributing to impairments in cognition and sleep in offspring through the influence of parental genotype and genetic nurture mechanisms. Methods A mouse model of partial Kmo deficiency, Kmo heterozygous (HET-Kmo +/–), was used to examine brain KMO activity, KYNA levels, and sleep behavior in HET-Kmo +/– compared to wild-type control (WT-Control) mice. Brain mitochondrial respiration was assessed, and KP metabolites and corticosterone levels were measured in breast milk. Behavioral assessments were conducted on wild-type offspring from two parental groups: (i) WT-Control from WT-Control parents, (ii) wild-type Kmo (WT-Kmo +/+) from Kmo heterozygous parents (HET-Kmo +/–). All mice were C57Bl/6J background strain. Adult female and male offspring underwent behavioral testing for learning, memory, anxiety-like behavior and sleep–wake patterns. Results HET-Kmo +/– mice exhibited reduced brain KMO activity, increased KYNA levels, and disrupted sleep architecture and electroencephalogram (EEG) power spectra. Mitochondrial respiration (Complex I and Complex II activity) and electron transport chain protein levels were impaired in the hippocampus of HET-Kmo +/– females. Breast milk from HET-Kmo +/– mothers increased kynurenine exposure during lactation but corticosterone levels were unchanged. Compared to WT-Control offspring, WT-Kmo +/+ females showed impaired spatial learning, heightened anxiety, reduced sleep and abnormal EEG spectral power. WT-Kmo +/+ males had deficits in reversal learning but no sleep disturbances or anxiety-like behaviors. Conclusions These findings suggest that Kmo deficiency impacts KP biochemistry, sleep behavior, and brain mitochondrial function. Even though WT-Kmo +/+ inherit identical genetic material as WT-Control, their development might be shaped by the parent’s physiology, behavior, or metabolic state influenced by their Kmo genotype, leading to phenotypic sex-specific differences in offspring.